Environmental sensitivity spatial analysis for oil spill mitigation in rote Ndao district waters - Dwi Ariyoga Gautama; Endang Koestati Sriharini; Yonvitner Yonvitner (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2024)
The marine ecosystems in the southern part of Rote Ndao District, within the Timor Sea, could be harmed by oil spills from ships or offshore rigs operated by oil and gas companies in the Timor Sea block, shared by Indonesia, Australia, and Timor Leste. The assessment using Environmental Sensitivity Index (ESI) maps using the thematic data. Areas identified as most sensitive to oil spills include West Rote district (Boa and Nembrala villages), and Southwest Rote district (Oeseli, Landu, and Manuk villages and Ndana islands). The beach type in Rote Ndao which is dominated by sloped sandy beach is a substrate type that is easy to clean from oil spill. Conversely, the biodiversity component has the highest sensitivity. The socio-economic components that are most sensitive to the effect of oil spills are the main sources of livelihood include seaweed cultivation, fisheries, and marine tourism. Oil spill mitigation in Rote Ndao must be focused on oil spill risk management in the hotspot area based on the environmental sensitivity index. A plan to prevent oil spills can be created, targeting these hotspots to establish an early warning system for effective mitigation.Keywords:Environmental sensitivity indexoil spillRote Ndaobiodiversityrisk management